Stress and strain distributions in the human hand-arm system using finite element analysis - Adewusi, Surajudeen; Thomas, Marc (International Journal of Engineering and Technology, 2017)
This study presents stress and strain distributions in the human hand-arm system exposed to vibrations using finite element (FE) models. Frequency weightings at shoulder, elbow, wrist and palm based on stress and strain distributions were proposed. The stress/strain-based frequency weightings around the shoulder and elbow are comparable with that reported in the International Organization for Standardization ISO 5349-1, Mechanical vibration and shockâ€“ Measurement and evaluation of human exposure to mechanical vibration â€“ part 1: General requirements, 2001. However, stress/strain-based frequency weightings around the palm and wrist are different above 20 Hz from the weighting reported by the International Standard Organization.Â This study suggests the need for different frequency weightings for the assessment of the potential injury of different components of the hand-arm vibration syndrome.